Peripheral neuromodulation for the treatment of refractory trigeminal neuralgia - Naum Shaparin; Karina Gritsenko; Diego Fernandez Garcia-Roves; Ushma Shah; Todd Schultz; Oscar DeLeon-Casasola (Pain Research and Management)
Trigeminal neuralgia is a type of orofacial pain that is diagnosed in 150,000 individuals each year, with an incidence of 12.6 per 100,000 person-years and a prevalence of 155 cases per 1,000,000 in the United States. Trigeminal neuralgia pain is characterized by sudden, severe, brief, stabbing or lancinating, recurrent episodes of pain in the distribution of one or more branches of the trigeminal nerve, which can cause significant suffering for the affected patient population.